Educative Web-Based Virtual as a Learning Media For Training Scientific Attitude In High School Student - Haka, Nukhbatul Bidayati; Sari, Maycha Erliana; Masya, Hardiyansyah; Rakhmawati, Ismi (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2024)
Media is important in learning, especially with the development of science and technology. This study aims to design and develop a virtual laboratory based on web education as a learning media and to train the scientific attitudes of high school students. The type of research used in Research and Development (R&D) refers to the nine stages of Borg and Gall. The feasibility test of web education uses a validation questionnaire of material experts, language experts, media experts, and educator response questionnaires. The study results showed that material experts comprised 87.5%, language experts comprised 94%, media experts comprised 91.5%, and educator response questionnaires comprised 85.33%. So, web-educative biology is a very feasible category. The effectiveness of the media in training scientific attitudes is known to have an average n-gain value of 0.59 (moderate) for the experimental class and 0.39 (moderate) for the control class. Based on the results of the t-independent test, a sig of 0.00 <α value (0.05) was obtained, which means that H1 is accepted and H0 is rejected. It is concluded that the web-based educational Virtual Laboratory is effective in training the scientific attitudes of high school students and is suitable for use as a biology learning medium.